Nanopore long-read RNAseq reveals widespread transcriptional variation among the surface receptors of individual B cells - Ashley Byrne (Nature Portfolio, 2017)
Short-read RNA-seq is limited in its ability to resolve complex transcript isoforms since it cannot sequence full-length cDNA. Here the authors use Oxford Nanopore MinION and their Mandalorion analysis pipeline to measure complex isoforms in B1a cells.